Epidemics in premodern Middle Eastern society and thought - Ayalon, Yaron (History compass, 2021)
This article examines thought about and responses to epidemics in the Middle East before the 19th century. Its focus is mostly on approaches to plagues, the responses of state officials to them, and people's reactions in the Ottoman period (16th-18th centuries), with some attention given to the early Islamic and Mamluk periods. Among issues explored are distribution of grain, price control measures, tax adjustments, and an array of other actions taken mostly locally, including quarantine. The latter referred primarily to the question of flight: whether it was permissible to leave a plague-ridden area, and how many people actually took such action. As I show here, flight was a common response despite prohibitions on the practice appearing in the Islamic plague literature.